Contrast-Kinetics-Resolved Whole-Heart Coronary MRA Using 3DPR - Lai, Peng (2010)
Slow contrast infusion was recently proposed for contrast-enhanced whole-heart coronary MR angiography (MRA). Current protocols use Cartesian k-space sampling with empirical acquisition delays, potentially resulting in suboptimal coronary artery delineation and image artifacts if there is a timing error. This study aimed to investigate the feasibility of using time-resolved three-dimensional projection reconstruction (3DPR) for whole-heart coronary MRA. With this method, data acquisition was started simultaneously with contrast injection. Sequential time frames were reconstructed by employing a sliding window scheme with temporal tornado filtering. Additionally, a self-timing method was developed to monitor contrast enhancement during a scan and automatically determine the peak enhancement time around which optimal temporal frames were reconstructed. Our preliminary results on 6 healthy volunteers showed that by using time-resolved 3DPR, the contrast kinetics of the coronary artery system throughout a scan could be retrospectively resolved and assessed. In addition, the blood signal dynamics predicted using self-timing was closely correlated to the true dynamics in time-resolved reconstruction. This approach is useful for optimizing delineation of each coronary artery and minimizing image artifacts for contrast-enhanced whole-heart MRA.